2018
DOI: 10.1016/j.jacc.2018.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in High-Intensity Statin Use Following Myocardial Infarction in the United States

Abstract: Despite recent efforts to reduce sex differences in guideline-recommended therapy, women continue to be less likely than men to fill a prescription for high-intensity statins following hospitalization for MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 27 publications
8
76
0
1
Order By: Relevance
“…However, this corresponds with data showing female patients often underestimate their risk of cardiovascular disease . Additionally, a recent study found that women were less likely than men to fill a prescription for a high‐intensity statin following a myocardial infarction . It has been theorized that this difference could be related to the atypical presentation of cardiovascular events among women.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, this corresponds with data showing female patients often underestimate their risk of cardiovascular disease . Additionally, a recent study found that women were less likely than men to fill a prescription for a high‐intensity statin following a myocardial infarction . It has been theorized that this difference could be related to the atypical presentation of cardiovascular events among women.…”
Section: Discussionsupporting
confidence: 73%
“…10 Additionally, a recent study found that women were less likely than men to fill a prescription for a high-intensity statin following a myocardial infarction. 11 It has been theorized that this difference could be related to the atypical 12 However, further study is needed to investigate other factors contributing to the disparity in gender outcomes within this clinic.…”
Section: Discussionmentioning
confidence: 98%
“…Cardiovascular disease (CVD) is recognized as the leading cause of death among both genders [1], but there are unique pathophysiological and clinical features of CVD in women [2,3]. In the United States of America (USA), gender disparities in CVD are long-standing and persistent in time to diagnosis [4,5], guideline-directed treatments [2,3,[6][7][8][9][10][11][12][13][14][15], and outcomes [2,3,[10][11][12][13][14]16], although the overall prevalence of CVD in women is less than in men (44.7 versus 51.2%) [1]. When considering racial/ethnic CVD prevalence, the highest CVD prevalence rates are among Black males (60.1%) and Black females (57.1%), while the lowest prevalence rates are among NH Asian males (47.4%) and NH Asian females (37.2%) [1].…”
Section: Introductionmentioning
confidence: 99%
“…8 -14 Of these, we are aware of only a few studies that extend beyond the year that the guideline was published and even then only include narrowly defined populations (eg, only privately insured and/or Medicare patients, those covered by a single insurer, those within 30 days postmyocardial infarction (MI)). 10,11,13,14 We examined nationally representative data for the years 2008 through 2016 to determine whether there has been an increase in use of statins in persons with a history of ASCVD following the publication of the ACC/AHA guideline in 2013. Prior studies have tended to focus on narrower samples whereas ours contains a nationally representative sample of adults with any history of ASCVD, the wider population targeted by the ACC/AHA guideline.…”
mentioning
confidence: 99%